Temperature profile of rice grain during its heating in the domestic microwave oven - Kumar, Ashok; Lata, Sneh; Kulshrestha, Rewa (Journal of Postharvest Technology, 2023)
Microwave puffing is an alternative of the sand and air puffing. Microwave heating of rice grain during its puffing in domestic microwave oven  was modeled using finite element based COMSOL multiphysics 3.3a software. The 3D-geometry, consisting oven, waveguide, turntable and  rice grain in oven, was drawn. A multiphysics model was developed by coupling the electromagnetic wave and general heat transfer modules.  The Maxwell’s equation of electromagnetics was solved for the electric field inside the oven cavity and the rice grain. The energy equation was  solved for the temperatures profile inside the rice grain. Uneven heating of rice was observed that was influenced by the placement of rice grain  on the turntable of the microwave oven. Rice grain, placed in the radial zones of 0 - 2.5 cm, 12.5-15 cm and 8.75-11.25 cm, did not absorb  sufficient microwave energy, which resulted in mostly unpuffed or semi puffed rice. Rice grains placed in the puffing zone of 3.75 to 6.25 cm  was absorbed sufficient energy and crossed glass transition temperature in 13-14 s, which resulted in mostly puffed rice. Apart from the location  of puffing zone and heating time, revolution of rice grain on the turn table and the distribution of electromagnetic field also influenced the heating  pattern.
Keywords: Microwave puffing; microwave power absorption density; rice puffing.